Prediction of Seepage Emanating from a Residue Disposal Facility for Various Closure Options - Govender, K.; van Zyl, A.; Bezuidenhout, N. (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
A source-term (also referred to as source) characterization study was completed in support of closure design and engineering for a residue disposal facility (RDF). The RDF contains different process waste streams from a zinc processing company in South Africa. The objective of the study was to develop a source-term model that simulates seepage fluxes and loads from the RDF footprint during the operational and closure phases. The integrated mass transfer model developed provided a mass loading per footprint area and was used as a source input to the numerical groundwater model. The model was developed to assess the incremental change of seepage fluxes and loads from the study area during operational and closure phases for various closure scenarios. The model was supported by detailed specialist flow and geochemical models which simulated specific processes. The specialist models used were Vadose/W for unsaturated flow modeling, Darcian equations for saturated flow modeling, and PHREEQC Version 2.7 for modeling of equilibrium reactions and identification of geochemical solubility controls on seepage quality.